Gargoylism. About of a case anatomic and clinical - Pizarro Flores, Manuel (1963)
The gargoylism or Pfaundler-Hurler's disease is a rare clinical entity on whose etiology is far from being fully elucidated. Metabolic, congenital and familial disorder, transmitted by recessive inheritance, was until recently considered a lipidosis, in that morphological alterations present "features" of ganglion cells.